民国电影检查的主题与问题1932-1937 ：以辱华、左翼、肉感为重点 = Issues and problems of film censorship in Republican China (1932-1937) : with a focus on Insulting Chinese, the left wing and sensuality - 王晓亚 Wang, Xiaoya (2018)
The voice of the film censorship in republican china was started in the folk, but in the process of being returned to the government step by step, it went to highly political and centralization, showing the characteristics of the bottom-up, and the necessity of the early examination as well as the political purpose.